Tool wear influence on surface roughness, burrs and cracks in milling unidirectional carbon fiber reinforced plastics (UD-CFRP) - Weizhou Wu; Shipeng Li; Xuda Qin; Guoyu Fu; Zhengwei Bao; Hao Li; Qing Zhao (Journal of Materials Research and Technology, 2024)
This study delves into the machining defects encountered during the milling of Carbon Fiber Reinforced Plastics (CFRP), with a special focus on fishbone-like cracks on the machined surface, which have never been focused before. Through a series of experiments, models for post-machining fiber burrs and matrix cracks were developed and analyzed, uncovering the causes of fishbone crack formation. The research reveals that the formation mechanisms of burrs vary with fiber orientation, burrs are not only from fiber bending under tool pressure but also from fiber buckling. Fishbone cracks are believed to be induced by growing burrs as the tool wear, and propagate along the in-plane and subsurface. Propagation downwards is along the fiber direction, while propagation inward is at an angle of approximately 40° ± 3°. This research is vital for enhancing the machining quality of composite materials and their engineering applications.